Comparação das estruturas entoativas do verbo imperativo em português e espanhol - Lapastina, Solange Vieira (2010)
This dissertation s objective is to confront the acoustic-phonetic analysis based on intoational characteristics recorded with a group of equal-value statements in Spanish and Portuguese results with the perceptive evaluation protocols of speech attitudes and acts application with the same statements group by Spanish and Brazilian judges. The statements were extracted and translated to Portuguese from CDs which come along with didactic books. All of the statements in which our research corpus consists are verbs on the affirmative imperative in Portuguese and Spanish. Through perception works, we investigated what is the speaker s interpretation to what is said and how such speech is received. The same way we studied native Brazilian Portuguese speeches, in the same discursive situations to compare their oral productions. The Portuguese statements recordings were made at the PCUSP s Radio and TV Studio and the obtained data analysis were made using the computer program PRAAT, which enabled us to analyze the respective statements melodic curve and the vowel where the f0 peak occurs. The prosodic study of such statements will help us to understand the differences between Portuguese and Spanish and how native speakers of those two languages realize and interpret it. The obtained results indicate an equal pattern between the to languages in what is concerned to statements with the same phonetic characteristics perception. These results indicate the subsidy relevance on acoustic-phonetic analysis for the languages teaching